ECONOMIC EFFICIENCY OF FIELD CROP PRODUCTION ON FAMILY FARMS IN THE AUTONOMOUS PROVINCE OF VOJVODINA - Munćan, Petar; Božić, Dragica; Bogdanov, Natalija (Economics of Agriculture, 2010)
Most of the field crop production of Serbia is located in the region of the Autonomous Province of Vojvodina. About 52% of the cereal-growing area and more than 92% of the industrial crop-growing area of Serbia are located in the Vojvodina Province. Corn, wheat, sunflower, soybean and sugar beet predominate in the sowing structure. The study focused on the economic efficiency of field crop production on family farms in Vojvodina during the period 2005-2009. The aim was to analyze family farms 6-20 ha in size oriented to the production of some major field crops. Although these farms accounted for only 16.4% of the total number of family farms in Vojvodina, they used about 45% of the total arable land. The survey method was used to sample the data on some major production parameters on the 50 family farms focused primarily on field crop production in Vojvodina during the five-year period (2005-2009). The data were used for calculation the gross margin for the field crops analyzed in order to determine the changes of the economic efficiency of the production of some major field crops.